PEMBERDAYAAN MASYARAKAT PADA PELESTARIAN SITUS BANGKAI KAPAL "USS LIBERTY", TULAMBEN, BALI - Sofwan Noerwidi (Berkala Arkeologi, 2007)
Indonesia as the largest maritime country in the world, is estimated to have 3000 sites containing underwater archaeological resources. But unfortunately, this great potential has not been managed (research and its preservation) optimally. Various conflicts of interest in the management of underwater archaeological resources have led to new thinking in the vision of conservation. Therefore, it is necessary to develop an alternative approach that can better accommodate the various interests of the local community. One model of approach that is oriented to local communities is the community empowerment model. Empowerment of local communities around archaeological sites can be realized in three aspects of empowerment, namely: empowerment in the fields of a) socio-culture, b) politics, and c) economy.